Left Atrial Volumetric/Mechanical Coupling Index: A Novel Predictor of Outcome in Heart Failure With Reduced Ejection Fraction. (January 2021) - Benfari, Giovanni; Essayagh, Benjamin; Nistri, Stefano; Maalouf, Joseph; Rossi, Andrea; Thapa, Prabin; Michelena, Hector I.; Enriquez-Sarano, Maurice
Abstract : Background: Left atrial assessment is complex, particularly in heart failure with reduced ejection fraction due to interactions with functional mitral regurgitation (FMR). Pilot data suggest that left atrial volumetric/mechanical coupling index (LACI) may be useful, but large outcome data are lacking. Methods: We enrolled a comprehensively characterized cohort of patients in sinus rhythm with heart failure with reduced ejection fraction diagnosis at Mayo Clinic from 2007 to 2011. Routinely measured left atrial volume index and tissue-doppler-imaging a' allowed LACI calculation as (left atrial volume index)/(tissue-doppler-imaging a'). Survival was the outcome measured. Results: The cohort's 4196 patients (69 [58–77] years, ejection fraction 40 [31–45]%) had mild FMR in 1505 and moderate-severe FMR in 1068. LACI was overall 5.06 (3.50–8.10) and increased with each FMR grade (3.86 [2.94–5.29] without FMR, 5.38 [3.80–8.02] with mild, 5.45 [1.49–8.07] with moderate/severe FMR; P <0.0001). At diagnosis, higher LACI was independently determined by more severe FMR and by higher left ventricular mass index, lower ejection fraction, higher E/e', and lower glomerular filtration rate (all P <0.0001). During follow-up 1588 (38%) patients died. In spline modeling, excess mortality appeared around LACI=6 and steeply increased thereafter (5-year survival 72±1% with LACI<6 and 49±2% with LACI ≥6, P <0.0001). Multivariable comprehensive adjustment showed LACI strong association with excess mortality (adjusted hazard ratio, 1.41 [1.23–1.61], P <0.0001 for LACI ≥6). Independent link to mortality persistent across FMR grades (adjusted hazard ratio, 1.45 [1.13–1.86], P =0.004 without FMR, 1.42 [1.16–1.77], P =0.0008 with mild FMR, and 1.38 [1.01–1.66], P =0.04 with moderate/severe FMR) without interaction ( P =0.3). LACI independent impact on outcome was incremental to that of left atrial volume index, tissue-doppler-imaging a', or any other characteristic including the Meta-Analysis Global Group in Chronic-score (least significant P =0.02). Conclusions: In this large cohort, left atrial volumetric/mechanical coupling measured by LACI in routine practice integrates the influence of several morphological/hemodynamic determinants but displays progressive deterioration with increasing FMR severity in heart failure with reduced ejection fraction. About outcome, higher LACI is strongly, independently, and incrementally associated with excess mortality, irrespective of FMR grade and in all subsets. Hence, LACI is a novel and critical measure in heart failure with reduced ejection fraction, quantifiable in routine practice, which should be integrated in prognostication and decision-making. Abstract : Supplemental Digital Content is available in the text.